Pengaruh Manfaat, Kemudahan Penggunaan, dan Risiko yang Dirasakan Terhadap Keputusan Pembelian Aktual pada Aplikasi Bibit - Nabilla Syaidatina Aisyah (Publikasi Indonesia, 2023)
Development in the field of investment and financial technology is inevitable. Financial technology at this time provides services for beginners in investing. This study aims to increase knowledge about the effect of perceived benefits, perceived risks, perceived ease of use, trust, and online purchase intent on actual purchases in making investment purchases on the Bibit application. Data collection was carried out by distributing questionnaires conducted from December 2022 to January 2023. Furthermore, this study used a non-probability sampling method with purposive sampling techniques, while the determination of the number of samples was carried out with a formula from Hair et al. (2019) so that the data that could be collected was 231 people. The data was processed using the Lisrel Structural Equation Model (SEM) to test the existing models in this study. The results of data processing show that perceived benefits have no influence on online purchase intention and actual purchase. Perceived risk has an influence on online purchase intention. Perceived risk has no effect on trust and actual purchases. Perceived ease of use has no effect on trust and online purchase intention. Trust has no influence on the actual purchase. Online purchase intention has a negative influence on actual purchases.